A narrative review of pediatric peripheral arterial aneurysms - Yashashwini Sudina, MS; Prajna B. Kota, MS, MCh; Vijaya Tourani, MD; Prem Chand Gupta, MS (JVS-Vascular Insights)
Background: Pediatric peripheral arterial aneurysms are uncommon and their natural history and management protocols are not well-defined. Methods: This is a single-center retrospective review of medical records of pediatric peripheral arterial aneurysms along with their treatment, outcomes and genetic studies. We also performed a systematic review of the literature on pediatric arterial aneurysms. Results: From our records we identified five aneurysms in five children involving the radial, facial, subclavian, costocervical trunk, and axillary arteries. All aneurysms were treated surgically with good outcomes and genetic studies were abnormal in four of the five patients. Histopathology was nonspecific for any etiology and showed myxoid degeneration of the tunica media for all aneurysms. This systematic review included 147 articles from 6484 publications that were used for synthesis. We included 195 children with 321 aneurysms in this analysis. There was a male preponderance (63.4%) with mean age of 6.3 years (range 2 days to 18 years). Iliac artery was most frequently affected (26.8%), followed by brachial artery (19.3%). Nearly one-third had bilateral aneurysms and 43% had aneurysms at multiple sites. Concurrent visceral aneurysms, predominantly aortic, renal, and coronary were seen in 55 children (37.4%). The commonest etiology was idiopathic (41%) followed by Kawasaki disease (23.5%) and infection (7.2%). Genetic testing was done for 14 children, with 7 having a contributing genetic component. Treatment protocols included medical management, open surgery, endovascular intervention, hybrid repairs, and observation only. Conclusions: Pediatric arterial aneurysms can be treated surgically with good outcomes and may often be associated with genetic abnormalities. The approach to treatment is diverse, and it is difficult to recommend a standardized protocol.